DIARRHEA IN CHILDREN: MAIN CAUSES AND WAYS OF TREATMENT - S.V. Bel'mer; T.V. Gasilina ("Paediatrician" Publishers LLC, 2010)
The article discusses main questions of diagnostics of diarrhea in children. Main cause of acute diarrhea is infection, mainly viral (rotavirus, etc.). Chronic diarrhea frequently has non-infectious origin. The need of multi-aspect diagnostics of diarrhea cause in children is related to the significance of treatment of main disease. Besides, treatment of chronic and acute diarrhea include major component: adsorbents based on smectite. In total treatment of diarrhea has to be complex with the use of dietotherapy and medications: mucocytoprotectors, regulators of motoric, pre- and probiotics. Key words: children, diarrhea, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):135-138)